High-speed observations of ultrasonic fragmentation and de-agglomeration process of free-floating intermetallics and oxide particles - Priyadarshi, Abhinav; Subroto, Tungky; Pericleous, Koulis A.; Eskin, Dmitry G.; Durodola, John; Tzanakis, Iakovos (Light metals 2022)
The need for lightweight and high-strength advance materials in the form of metal-matrix composites with micron-sized particulate reinforcements has received considerable attention within automotive and aerospace industry. Ultrasonic melt treatment of Al alloys offers a sustainable and eco-friendly approach to produce structural refinement through enhanced heterogeneous nucleation obtained from combined effect of sono-fragmentation of primary intermetallic/dendrites and de-agglomeration of non-metallic oxides/inclusions. However, owing to complexity of the process, understanding of the underlying mechanisms behind these effects is still rudimentary and lacks experimental evidences. In this paper, an insight into the underlying mechanism of fragmentation and de-agglomeration of Al3Zr intermetallic and Mg0 oxide particles, respectively, in water is presented. Real-time high-speed imaging was performed to discern the dynamic interaction of cavitation with free-floating particles in a controlled ultrasonic environment. In situ observations revealed that intermetallic breakage primarily occurs due to propagating shock waves, whereas the oxide de-agglomeration happens through microbubble cluster collapses close to the agglomerate.